Optimalisasi Strategi Pemasaran melalui Digital Marketing pada UMKM Cendol Dawet Sagu Lasah Desa Tawangargo - Fahmi Junaidi; Rifqi Zaenal Abidin; Any Fatmawati; Aisya (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The micro, small and medium enterprise (MSME) industry Cendol Dawet Sagu Lasah is a beverage business made from rice flour that forms an oval shape because it is printed with a cendol printer. In conducting marketing activities, Cendol Dawet Sagu Lasah uses the traditional system by means of mobile marketing or door to door to several neighboring villages. Through the applied marketing strategy, relatively few sales results are obtained because it has a limited scope of consumers. This happens because the reach of marketing information is limited to consumers. So this study aims to optimize innovative, effective and efficient marketing strategies through the use of digital marketing as an effort to increase selling power to the maximum. This service and research uses qualitative methods by going through the stages of a survey of business actors. In the implementation, mentoring and training were carried out for partners by optimizing facilities on social media such as Facebook, Instagram, Youtube and Whats App Business which can be accessed via smartphones. The expected output of this research can produce more innovative, effective and efficient strategies. So that it can attract consumers and business actors to know the positive impact on the optimal use of social media in the business sector